English for business purposes: Designing media for vocational high school students - Anugerahwati, Mirjam; Rosyidah, Umniyah Juman; Abargiel, Kauna Bismie; Wijaya, Robby; Laksmi, Ekaning Dewanti; Kusdiyanti, Heny (UPT Bahasa Universitas Tanjungpura, 2025)
English for Specific Purposes (ESP) has become a teaching strategy employed by teachers to support vocational education. However, English instruction in vocational high schools (SMK), especially in Trenggalek Regency, East Java, Indonesia has yet to fully address ESP aspects. Therefore, this study aims to develop an ESP book based on a gamification model and evaluate its effectiveness using ANOVA tests. The research utilized the ADDIE development model, with a private SMK in Trenggalek Regency as the primary research subject. The findings indicate that the book is highly suitable for use, scoring 85% for attractiveness and 84% for appropriateness. Based on these results, it can be concluded that the book is effective for teaching English in the context of entrepreneurship and business at vocational high schools, confirming its suitability for business-oriented English learning. These findings highlight gamified ESP materials